2020
DOI: 10.2217/pgs-2020-0120
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Severe Toxicity in an African–American Patient Receiving FOLFOX Carrying Uncommon Allelic Variants in DPYD

Abstract: Cancers of the colon are commonly treated with fluoropyrimidines, which often cause severe toxicities in patients with certain variants in DPYD. Y186C (rs115232898) and a variant in the 3′ untranslated region (rs12132152) are uncommon alleles previously observed in African–Americans. An African–American female underwent 5-fluorouracil-based therapy (400 mg/m2 bolus, 1200 mg/m2/day over 46 h). The patient experienced severe pancytopenia after the first cycle. After 5-fluorouracil (5-FU) dose reduction (600 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Here, in the absence of one of the four most common DPYD variants, we first screened patients with U ≥ 16 μg/L and ancestors of African origin for the variant c.557A>G (rs115232898) and then performed complete sequencing for patients with U ≥ 16 μg/L in the absence of this latter variant. Among the nine additional DPYD variants identified among 52 patients, the sole listed as deleterious by both the CPIC and SIFT database was the variant c.557A>G. This variant, which is relatively frequent in Africans (frequency between 1.6 and 9.1% according to studies), 35–37 was shown to be associated with decreased DPD activity in an isogenic mammalian system 35 and identified in three patients experiencing severe toxicity after 5FU treatment 38–40 . In our study, the addition of this fifth variant (to the four systematically sought) allowed us to reach significance for the independent association between U and presence of a DPYD genetic variant (Table S5).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Here, in the absence of one of the four most common DPYD variants, we first screened patients with U ≥ 16 μg/L and ancestors of African origin for the variant c.557A>G (rs115232898) and then performed complete sequencing for patients with U ≥ 16 μg/L in the absence of this latter variant. Among the nine additional DPYD variants identified among 52 patients, the sole listed as deleterious by both the CPIC and SIFT database was the variant c.557A>G. This variant, which is relatively frequent in Africans (frequency between 1.6 and 9.1% according to studies), 35–37 was shown to be associated with decreased DPD activity in an isogenic mammalian system 35 and identified in three patients experiencing severe toxicity after 5FU treatment 38–40 . In our study, the addition of this fifth variant (to the four systematically sought) allowed us to reach significance for the independent association between U and presence of a DPYD genetic variant (Table S5).…”
Section: Discussionmentioning
confidence: 78%
“…Among the nine additional DPYD variants identified among 52 patients, the sole listed as deleterious by both the CPIC and SIFT database was the variant c.557A>G. This variant, which is relatively frequent in Africans (frequency between 1.6 and 9.1% according to studies), [35][36][37] was shown to be associated with decreased DPD activity in an isogenic mammalian system 35 and identified in three patients experiencing severe toxicity after 5FU treatment. [38][39][40] In our study, the addition of this fifth variant (to the four systematically sought) allowed us to reach significance for the independent association between U and presence of a DPYD genetic variant (Table S5). These data, combined with the fact that this variant was identified here in 3/3 patients with U ≥ 16 μg/L and African ancestors and in 7/111 DPD-deficient patients in another large French cohort, 26 suggest that screening of this variant could be of interest in France, at least for patients with African ancestors.…”
Section: Discussionmentioning
confidence: 96%
“…Our systematic review has identified 3 case studies detecting the c.557A>G variant (rs115232898, p.Tyr186Cys) in African Americans with severe 5-FU-related toxicity [60][61][62] , one of which was fatal 61 . In addition, in an editorial which was not eligible for inclusion in our systematic review, this variant was reported in an African-Caribbean patient with severe 5-FU-related toxicity 94 .…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we have undertaken a comprehensive in silico evaluation of the likely functional consequences of the mutations, but further functional evaluation will be needed for many of the variants. Notably, our systematic review has identified a number of patients carrying more than one DPYD variant and in particular one African-American carrying 2 loss-of-function variants c.295_298delTCAT and c.1898delC in addition to the decreased function variant c.557A>G (Supplementary Results) 62 ; how the co-expression of functional DPYD variants affects overall DPD activity and the consequences for the severity of fluoropyrimidine-related toxicity remains to be elucidated. Our focus has been on the DPYD gene, but there are other potential genes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation